Awarness and attitude about dental treatments Among middle school students of chennai - JEMBULINGAM SABARATHINAM; DR.GEO MANI; DR.DEEPA GURUNATHAN (International Journal of Pharma and Bio Sciences, 2016)
Dental problems which is not diagnosed and treated in early stages of the problem might put forward a potential threat to the tooth in the forthcoming days. So early dental treatments plays a significant role in preventing adverse effects of such dental problems. Thereby it is very important to be aware of dental treatments in this modern world in order to utilize them in a beneficial manner. The purpose of the study was to know about the awareness and attitude about dental procedures among private school students and check whether the school students are aware of dental procedures and to find their Attitude about dental procedures among the students. This study was a questionnaire based study done on middle schools of south Indian population with proper permissions from the head of the institution. The questionnaire had 13 questions relating to the attitude and knowledge about dental procedures. Reponses were collected, later the data was analyzed using SPSS software (version 14).It was found to be that the most frequently done procedure is scaling while the fear for dentist is mostly persuaded because of the fear of cost of treatment and fear of needles. And children these days are not aware of modern techniques like dental implants and think that these dental treatments cannot change their aesthetic looks. Children in the modern world are aware of basic procedures .but there exist a circle of students who don’t even have the basic knowledge about these procedures. Nowadays even though technology is developing, the students are not aware of the recent updated modern dental treatments in the field of dentistry which could be very much beneficial to them in the current situation because of the changing lifestyle patterns and eating habits.